2016
DOI: 10.1186/s40643-016-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of silver nanoparticles from Origanum majorana and Citrus sinensis leaf and their antibacterial activity: a green chemistry approach

Abstract: Background: Silver nanoparticles (SNPs) play important role in the field of optics and electronics and also as a novel antibacterial agents. Here, we report a simple and green method for the biosynthesis of SNPs using aqueous leaf extract of Origanum majorana and Citrus sinensis as a novel bio source of cost-effective, non-hazardous reducing, and stabilizing agents. A 3 mM solution of silver nitrate was prepared. Five milliliter aqueous leaf extract was slowly added to 20 ml silver salt solution (3 mM) with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Some peaks of the ORE (e.g., the 1596 and 1041 cm −1 ) show a slight shift to lower wavenumbers in the case of Ag/ORE sample. This shift is in accordance with [ 36 ] and indicates possible successful interaction between the formed Ag NPs and some components of ORE.…”
Section: Resultssupporting
confidence: 91%
“…Some peaks of the ORE (e.g., the 1596 and 1041 cm −1 ) show a slight shift to lower wavenumbers in the case of Ag/ORE sample. This shift is in accordance with [ 36 ] and indicates possible successful interaction between the formed Ag NPs and some components of ORE.…”
Section: Resultssupporting
confidence: 91%
“…The existence of 1252 cm −1 peak in AgNPs FTIR spectrum represented the existence of C–N stretching vibration bond of aromatic amines 47 . The existence of peak at 1085 cm −1 in the FTIR spectrum indicated C–O–H stretching bond in primary and secondary alcohols 48 . The bands at 986 cm −1 and 864 cm −1 referring to the C–N and N–H stretching vibration bonds; respectively of primary amines suggesting the primary amine groups may involved in NPs synthesis 49 and could present in capping agents of synthesized NPs.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that the principal biomolecules present in plant extracts responsible for the reduction of metal ions to form NPs are proteins, polyphenols, vitamins and sugars, in particular L‐ascorbic acid, caffeic acid, gallic acid and quercetin . However, most synthesis methods utilizing these biomolecules require high temperatures such as the synthesis using starch and glucose as reducing agents at high temperature for 20 h or the synthesis using L‐ascorbic acid at 80 °C or they require microwave assistance . Moreover these methods are influenced by several variables which are difficult to control and can affect the method reproducibility .…”
Section: Introductionmentioning
confidence: 99%